A study on enhancement of wayfinding strategies in Kuala Lumpur International Airport 2 (KLIA2) / Nor Hafizudin Noriman and Amirul Amin Ismail - Noriman, Nor Hafizudin; Ismail, Amirul Amin (2018)
Wayfinding can best be described as spatial problem-solving. It is one of the main factors when passengers rate their experiences at the airport terminal. Passengers and visitors at the terminals frequently complain they have difficulties in finding their way through the complex structures and most of them are associated closely to puzzling signage. The objective of this study is to identify issues that lead to poor performance as evaluated on current KLIA2 terminal wayfinding system. This paper focuses specifically on visual information elements such as the font, colour, symbols and size. Kuala Lumpur International Airport 2 (KLIA2) is selected as the case study for this research. As it is popularly known as the world’s largest low-cost carrier terminal, providing a comprehensive and effective wayfinding could be a monumental task for KLIA2. Interview sessions and observation on respondents were done and documented to analyse the passengers’ movement and feedback. The study shows that KLIA2 signage systems need colossal improvement. Results have shown that signage in KLIA2 is fairly visible but below average when it comes to readability and requires improvement in that aspect. Comprehensive wayfinding will not only deliver significant improvement to KLIA2’s existing signage specification but it will also save time and enhance the users’ experience and stigma towards low-cost carrier terminals.